Estudios Interculturales desde el Sur: procesos, debates y propuestas - Samaniego, Mario (Ariadna Ediciones, 2021)
We are living in a time marked by crises of different natures and challenging contradictions. A time where the vital, environmental, health, economic and social crisis marks the rhythm of events, the morphology of imaginaries and the dispositions towards others and oneself. The situation described acquires particular edges in the Wallmapu, the territory in which this book arises; in which their ideas and proposals are directly or indirectly rooted, since, in addition to the global crisis indicated, the history of this territory is marked by injustice, contempt, conflict and the lack of conditions and provisions to productively channel the conflict as a constant that accounts for its dynamics The coordinates that we have just indicated delineate the objectives and expectations of this work, which arises academically and socially within the Master in Intercultural Studies of the Catholic University of Temuco, an academic unit linked to the Doctorate in Intercultural Studies and the Research Center in Inter-ethnic and Intercultural Studies of the same university, which share a main objective: to respond to the historical, socio-cultural and territorial conflicts of Wallmapu, taking into account and dialoguing with contexts that live similar situations, all they framed and conditioned by the processes of globalization.